"People Treated Me with Equality": Indigenous Australians Visiting the Soviet Bloc during the Cold War. (1st November 2016) - Piccini, Jon
Abstract : This paper discusses the entwining of Australian communists, trade unions and indigenous activists: a much-studied topic. However, I approach it from a "transnational" perspective, unearthing intersections between global ideas and local activism through a case study of how the Communist Party of Australia (CPA) and trade union bodies under its control or influence sent particular indigenous activists abroad during the 1950s and 1960s. It looks at why the CPA would invest the time and money in these trips, and what indigenous Australians thought they could get out of them. In so doing, it explores the possibilities and limits of this form of globally-centred solidarity, and adds a new dimension to our understanding of international communist and trade union politics.